Pharmacy-faculty work-life balance and career satisfaction: Comparison of national survey results from 2012 and 2018 - Mitchell J. Barnett; Tristan Lindfelt; Shadi Doroudgar; Emily Chan; Eric J. Ip (Exploratory Research in Clinical and Social Pharmacy, 2022)
Background: Changes in demographics and composition of pharmacy faculty, along with faculty perceived stress, work-life balance and career satisfaction have yet to be fully documented. Objective: To compare recent results from a national survey of work-life balance and career satisfaction of United States (U.S.) pharmacy faculty with results obtained from a similar survey from 2012. Methods: A 46-item anonymous survey administered via Qualtrics (Provo, UT) was sent to members of the American Association of Colleges of Pharmacy (AACP) in 2018. Information regarding demographics, stress, work-life balance, career satisfaction and intent to leave academia was collected. Although not part of the previous survey, participant information related to bullying and abuse in the pharmacy academic work was also gathered. While actual p-values are reported for all comparisons, a more conservative p-value of 0.01 was chosen a priori to indicate significance as multiple comparisons were made. Results: A total of 1090 pharmacy faculty completed the survey, comparable to the number obtained in 2012 (n = 811). Overall response rates were similar for both years. The majority of pharmacy faculty in 2018 were female, white, married or with partner, worked in a pharmacy practice department and for a public institution. Notable differences between surveys included an increase in females, more associate professors and an increase in non-white faculty in 2018, relative to 2012. Stress, as measured by mean Perceived Stress Scale (PSS) scores was also significantly higher in 2018 (16.0 ± 6.6 vs. 13.5 ± 6.7, p < 0.01) relative to 2012. Faculty from 2018 were significantly less likely to report an intention to remain in academia (61.8% vs 86.3%, p < 0.01), relative to 2012. A sizable number of pharmacy faculty surveyed in 2018 also reported observing or experiencing hostility in the workplace, which included either bullying or verbal or physical abuse. Conclusions: The makeup of pharmacy educators has evolved quickly over the last several years to comprise more female and associate professors who work within a pharmacy practice department. Also noteworthy is the significant increase in self-reported stress over the six-year timeframe. The direct implications of these findings are unknown but suggest that pharmacy academia is maturing in rank and changing to reflect the current pharmacy workforce (i.e., more females and additional clinical practice roles). Increases in responsibility likely accompany these maturing roles and may, along with other factors, contribute to the observed changes in the reported stress levels among faculty. Further research is called for regarding the reported hostility in pharmacy academic workplace and dovetails with concurrent work being done on citizenship and organizational citizenship behavior among pharmacy faculty. Findings of the study may aid pharmacy school administrators and stakeholders with plans to recruit, develop and retain faculty.